Influence of Ammonium Sulfate, Diesel Oil, and Surfactant on Glyphosate Activity in Purple Nutsedge - Suwanketnikom, Rungsit (Agriculture and Natural Resources, 1998)
Effects of additives on 14C-glyphosate penetration into purple nutsedge leaves and efficacy of glyphosate for purple nutsedge control were examined in 2 weeks old plants. It was found that the addition of (NH4)2SO4 at 1.0 % (v/v) + diesel oil at 1.0 % (v/v) + Tendal at 1.0 % (v/v) increased 14C-glyphosate penetration into nutsedge leaves more than the addition of either one. (NH4)2SO4 at 1.0 % + diesel oil at 1.0 % + Tendal at 0.12 or 0.25 % increased phytotoxicity of glyphosate at 0.5 and 0.75 kg ae/ha on the weed, in the greenhouse. Additives did not enhance glyphosate activity by reducing number of nutsedge tubers.